EFEKTIVITAS PENILAIAN KINERJA: Studi Kasus pada Pegawai Negeri Sipil di Kelompok Program dan Evaluasi Pusat Penyuluhan Pertanian Badan Penyuluhan dan Pengembangan Sumber Daya Manusia Pertanian Kementerian Pertanian RI - Alham Fataka Mulkika, (2022)
The world is now entering the globalization era. Company is forced to look for skilled workers that increasing the company's performance including Indonesian government. Through constitution no. 5 year 2014, the government employ state civil apparatus (ASN) which is divided by two namely government employee (PNS) and government employee with work agreement (PPPK). In constitution no. 46 year 2011, ASN work performance appraised by using employee work goals (SKP). This research goal is to analyze the effectivity of work performance appraisal in Performance Appraisal Effectivity (Case Study of Government Employee at Program and Evaluation Division Agricultural Center of Counseling Agency for Agricultural Extension and Human Resource Development Ministry of Agriculture of the Republic of Indonesia. Method used in this research is qualitative with 7 participants. The result shows that the work performance appraisal process in Program and Evaluation Group is working effectively given that 5 indicators which is the appraisal itself, linkages, sensitivity, practically, acceptable is effective and 1 indicator which is reliability is show ineffective.